If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 2 = y + -12 Reorder the terms: 2 + 8y = y + -12 Reorder the terms: 2 + 8y = -12 + y Solving 2 + 8y = -12 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 2 + 8y + -1y = -12 + y + -1y Combine like terms: 8y + -1y = 7y 2 + 7y = -12 + y + -1y Combine like terms: y + -1y = 0 2 + 7y = -12 + 0 2 + 7y = -12 Add '-2' to each side of the equation. 2 + -2 + 7y = -12 + -2 Combine like terms: 2 + -2 = 0 0 + 7y = -12 + -2 7y = -12 + -2 Combine like terms: -12 + -2 = -14 7y = -14 Divide each side by '7'. y = -2 Simplifying y = -2
| -5/8(16w-25)=35 | | 6x^2=5x-4 | | 3=12-15x | | 9x+2y=90 | | -307=6b+-7(-5b+-3) | | t^2-9t+18= | | -(1+8p)-6p=-3p-23 | | (5/6)x=5 | | (3-i)-(-4+9i)= | | 6m+-6(7+-3m)=102 | | -9/.6 | | -9/3/5 | | 15h=10h+80 | | 6z+11=59 | | (2x)(2x)=x+20 | | 5/5*2(6-2) | | 4+logx=10 | | 6x=330 | | 6x=10y+60 | | 15y^3-35y^2-30y= | | -7(x)=7 | | 7(x)=-7 | | u/-3=-4.2 | | s/2=3.02 | | b-2=5.9 | | (0.3x+0.6)=1.44 | | y+3.43=18.63 | | 4y^2+8y+16=0 | | c/-2=0.43 | | c-9.77=3.9 | | 20x=24x+8 | | 0.93=-p |